INTERPERSONAL CONFLICT AND ORGANIZATIONAL POLITIC AS JOB PERFORMANCE’S PREDICTORS OF BTN SHARIA OFFICERS - Abrista Devi; Ilham Wahyudi; Muchlis Muchlis; Nisa Gettar Sukma Sari (Univeristas Islam Bandung, 2022)
This study is addressed to investigate the impact of interpersonal conflict and organizational politics toward job-strain and employee’s performance of BTN (Bank Tabungan Negara) sharia, Bogor. Hybrid model of PLS were developed with the basis of an extensive literature review, the model also will be tested to obtain an empirical insight about the hypothesized impact. The data were collected from 215 employees who works in BTN Sharia for minimum a year. Performance data were also obtained from employee’s self-evaluation. This study employs quantitative approach with SEM-PLS (Structural Equation Modeling – Partial Least Square) methodology. The findings show that interpersonal conflict and organizational politics have positive and significant impact to the job strain, and interpersonal conflict has direct and indirect impact to job performance. There was no evidence that job strain moderated the effects of organizational politics to job performance. In addition, this study implies that the management of BTN sharia requires to maintain on manageable interpersonal conflict and good quality of organizational politics to achieve lessen job strain and boost job performance of their employee.